Trust and reciprocity in the investment game with indirect reward - Werner Güth; Manfred Königstein; Nadège Marchand; Klaus Nehring (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Experimental studies have shown that trust and reciprocity are effective in increasing efficiency when complete contracting is infeasible. One example is the study by Berg et al. (1995) of the investment game. In this game the person who receives the investment is the one who may reward the investor. This is a direct reward game. Similar to Dufwenberg et al. (2000) it is investigated to what extent trust and reward are still observable when reward is indirect; i.e., when the investor may only be rewarded by a third person who did not receive his investment. Furthermore we investigate the influence of social comparison (information about other players' investments). Our main finding is that mainly indirect reward reduces significantly mutual cooperation.
urn:nbn:de:kobv:11-10048367
Keywords: 330